Academic encouragement and academic wellbeing: Mediating roles of grit and hope - EKŞİ, HALİL (My University, 2023)
Academic encouragement provides opportunities for individuals to achieve their educational objectives and influences both academic satisfaction and academic self-efficacy of individuals. In this study, academic self-efficacy and academic satisfaction constitute academic wellbeing. There is a gap in the literature on which concepts of academic encouragement predict academic wellbeing. This demonstrates the originality of the research. In this direction, there are two main purposes in this study. The first of these aims is to adapt the Academic Encouragement Scale to Turkish culture. The second aim of the study is to analyze the relationship between academic encouragement, hope, grit, and academic wellbeing. Based on these two purposes, data were collected from 731 Turkish participants using the Academic Encouragement Scale, Academic Self-Efficacy Scale, Academic Satisfaction Scale, Dispositional Hope Scale, and Short Grit Scale. Confirmatory Factor Analysis (CFA) revealed that the two-factor structure of the original scale was preserved in Turkish culture. The structural equation modeling (SEM) analysis showed that grit and hope played a mediating role in the relationship between academic encouragement and academic wellbeing. The bootstrapping analysis results confirmed the importance of indirect effects. In this context, some pedagogical implications were discussed at the end of the study, and suggestions were provided accordingly.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; Temel Bilimler (SCI); Natural Sciences (SCI); PSYCHOLOGY; Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; General Psychology; Social Sciences & Humanities; Academic encouragement; academic wellbeing; grit; hope